2017
DOI: 10.1002/jcp.25980
|View full text |Cite
|
Sign up to set email alerts
|

Surface functionalized magnetic nanoparticles shift cell behavior with on/off magnetic fields

Abstract: Magnetic nanoparticles (MNPs) are used as contrast agents and targeted drug delivery systems (TDDS) due to their favorable size, surface charge, and magnetic properties. Unfortunately, the toxicity associated with MNPs limits their biological applications. Surface functionalization of MNPs with selective polymers alters the surface chemistry to impart better biocompatibility. We report the preparation of surface functionalized MNPs using iron oxide NPs (MNPs), poly (lactic-co-glycolic acid) (PLGA), and sodium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 45 publications
0
6
0
1
Order By: Relevance
“…319 In another case, the mechanical and physiological properties of fibroblasts were measured as a function of intracellular uptake of biocompatible magnetic nanoparticles and the applied magnetic field. 320 Various nanoparticle systems have also been deployed as intracellular temperature probes. 321 In one report, temperatureresponsive nanodiamonds of approximately 100 nm were introduced into cells via nanowires.…”
Section: Cargo Categories For Intracellular Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…319 In another case, the mechanical and physiological properties of fibroblasts were measured as a function of intracellular uptake of biocompatible magnetic nanoparticles and the applied magnetic field. 320 Various nanoparticle systems have also been deployed as intracellular temperature probes. 321 In one report, temperatureresponsive nanodiamonds of approximately 100 nm were introduced into cells via nanowires.…”
Section: Cargo Categories For Intracellular Deliverymentioning
confidence: 99%
“…The magnetic core enables their uptake and localization to be tracked by MRI . In another case, the mechanical and physiological properties of fibroblasts were measured as a function of intracellular uptake of biocompatible magnetic nanoparticles and the applied magnetic field …”
Section: Intracellular Delivery Cargo and Applicationsmentioning
confidence: 99%
“…磁性纳米颗粒被大量应用于生物医学领域, 在不 同的应用方式下, 磁性材料的形态以及存在环境也是 不同的. 例如将磁性纳米颗粒组装到细胞上实现通过 外磁场对细胞的调控 [48] , 或者研究细胞不同包覆的磁 性纳米颗粒吞噬能力的差别 [49] , 以及磁性纳米颗粒在 细胞中的降解过程 [50] , 这些种种研究都涉及对于材料 磁性的评估. 由于纳米磁性颗粒在被吞噬到细胞内部 之后, 其聚集状态会发生改变, 有研究还发现磁性纳 米材料被不同器官细胞吞噬后其降解过程都会有所差 异 [51] , 因此我们需要对这些生理环境中的磁性材料进…”
Section: 类生理环境中磁性纳米颗粒磁性测量算 法验证unclassified
“…First, PLGA as a drug delivery system is an FDA-approved polymer that has been widely used in therapeutic applications due to its many advantages, which include biodegradability, biocompatibility, lower cytotoxicity, and excellent pharmacokinetic properties. Furthermore, our group and other researchers 9,10 have reported that superparamagnetic iron oxide nanoparticles can be loaded into the PLGA polymeric matrix to obtain magnetic PLGA nanoparticles, which can easily reach the area of the targeted location and accumulate in targeted tissues/cells under the application of an external magnetic field. Second, a cationic polymer, polyethylenimine (PEI) with a molecular weight of 25 kDa, is a known cationic polymer used as the golden standard in gene transfection.…”
Section: Introductionmentioning
confidence: 97%